(untitled) (Altre Modernità, 2009)
During the XX, literary magazines were the elected places for experimenting in literature and for spreading cultural and political manifestoes, but in the XXI print seems to loose its appeal. Online literary magazines begin publishing important writers and interesting new ones. Besides they deal with the most significant themes of our time. El Ghibli - rivista online di letteratura della migrazione, that really promotes migrant writers in Italy, is elected as a case study. This article describes its essential features and verifies its position among Italian literature and national cultural movements. Moreover, it is a preliminary study of the magazine which is a quite original issue within the Italian milieu.